Optimasi Campuran Manitol-Sukrosa Untuk Tablet Hisap Ekstrak Daun Dewa (Gynura Procumbens (Lour) Merr)) Secara Granulasi Basah Dengan Metode Simplex Lattice Design - Youstiana Dwi Rusita (Jurnal Kebidanan dan Kesehatan Tradisional, 2016)
Abstract: Dewa Leaves, Lozenges, Simplex Lattice Design. Dewa is an Indonesian traditional medicinal plants are efficacious among others to the tonsils. Dewa leaf extract can be prepared as lozenges because it is more practical and effective than the traditional way in the form of infusion. This study aimed to get the optimum formula mannitol - sucrose using the simplex lattice design that has more value than triall error. Dewa leaf aqueous extract obtained by maceration leaf powder dewa with 70% ethanol and then evaporated to obtain a thick extract is dried with aerosil. This study is based on the method simplex lattice design with two components, namely FI (100% mannitol), F II (100% sucrose), F III (50% mannitol: 50% sucrose). The method used in the manufacture of leaf extract lozenges Dewa was wet granulation using the binder PVP. The granules tested flow rate, compactibility and granules ditablet to test the taste responses. Of the value of the response characteristics of the granules obtained the largest total selected as the optimum formula. Furthermore ditablet and tested physical properties which include uniformity of weight, hardness and friability of tablets. Data of physical properties of the granules suction of the optimum formula theoretically and statistically tested using the t test (T-test). The results showed that the optimum formula derived from a mixture of mannitol 70% - sucrosa 30%. From the results of the t test (T-test) and compactibility flow rate did not different significantly betwen theoretical experiment. To test the taste responses acceptable 98% of respondents. Dewa leaf extract lozenges optimum formula produced meets the physical properties of the tablet.